Analisis Kultur Sekolah dalam Pembentukan Etika Siswa - Lewis Laana; Ahmad Atang (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2026)
This study aims to analyze the role of school culture in shaping students’ ethical behavior and to identify the supporting and inhibiting factors in the process. The research employed a qualitative approach using a case study method conducted at SMA Negeri 2 Kalabahi. Data were collected through observation, interviews, and documentation involving the principal, teachers, and students. Data analysis was carried out through data reduction, data display, and conclusion drawing. The findings reveal that a strong and positive school culture significantly contributes to shaping students’ ethical behavior. This is reflected in the implementation of school vision and mission, character-building programs, integration of ethical values into the curriculum, and teachers’ role as role models. Co-curricular and extracurricular activities also reinforce moral internalization among students. Supporting factors include clear school policies, collaboration with external stakeholders, and active participation of school members. Meanwhile, inhibiting factors include external environmental influences, limited resources, and lack of parental involvement. This study highlights that school culture plays a strategic role in sustainably developing students’ ethical behavior.